Contribution of Intensity of Participation in Psychoeducational Group Guidance to Academic Emotions - Rahmawati, Weni Kurnia; Isriyah, Mudafiatun (Bulletin of Counseling and Psychotherapy, 2025)
This study aims to determine the contribution of the intensity of participation in psychoeducational group guidance to the academic emotions of students in Jember Islamic boarding schools. Academic emotions play an important role in determining the quality of students' learning, while psychoeducational group guidance provides space for students to recognize, express, and manage their emotions positively in the context of learning. This study uses a quantitative approach with a simple linear regression design. The population in this study were students who actively participated in group guidance activities in several Islamic boarding schools in Jember, with samples selected purposively. The instruments used were a questionnaire on the intensity of participation and an academic emotion scale that had been tested for validity and reliability. The results of the regression analysis showed that the intensity of participation in psychoeducational group guidance contributed significantly to students' academic emotions (p <0.05), with a contribution of 30% (R² = 0.30). This finding indicates that the more intense the participation of students in group guidance activities, the more positive the academic emotions they have. This study recommends that Islamic boarding schools integrate psychoeducational programs more systematically in student guidance activities.